1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Simultaneous equation

  1. Jan 24, 2010 #1
    I have just tried to solve the following simultaneous equation.

    x + 2y = 5
    x squared + y squared = 36

    I guess that the 1st step is to rearrange the 1st equation to give:

    x = 5 - 2y

    From that point onwards I have no idea what to do! Can anybody guide me through this?
    Thanks a lot!
     
  2. jcsd
  3. Jan 24, 2010 #2
    Substitute x with (5 - 2y) in the second equation to give:
    [tex]
    (5 - 2y)^2 + y^2 = 36
    [/tex]
    That's how to solve almost all simultaneous equations; the idea is to eliminate one variable in one of the equations so as to obtain an equation solely in terms of one variable, which can then be solved.
    Carry on.
     
  4. Jan 24, 2010 #3
    so...
    (5 - 2y) x (5 - 2y) + y squared = 36
    multipying out the brackets gives us:
    (25 - 10y - 10y + 4y) + y squared = 36
    so...
    (25 - 16y) + y squared = 36
    I've had a long hrad think at this stage and i'm stuck again! Am I going in the right direction?
    Thanks for your help!
     
  5. Jan 24, 2010 #4
    Yes, you are going in the right direction...but you made a mistake in expanding the brackets.
    [tex](5 - 2y)^2 + y^2 = 36[/tex]
    [tex](25 - 20y + 4y^2) + y^2 = 36[/tex]
    [tex]5y^2 - 20y + 25 = 36[/tex]
    [tex]5y^2 - 20y - 11 = 0[/tex]
    Now its just a matter of solving for y from this quadratic equation.
     
  6. Jan 24, 2010 #5
    just going back to the expanding of the brackets, i worked it outr as follows:
    (5 - 2y) x (5 - 2y)
    so..
    5 x 5 = 25
    5 x -2y = -10y
    -2y x 5 = -10y
    -2y x -2y = 4y (why does this equal 4y squared?)
    By the way, how do you type the little 2 tyat indicated squared?
    Thanks again
     
  7. Jan 24, 2010 #6
    because a minus x a minus is a plus. -2 x -2 = 4
    y x y = y^2

    so -2y x -2y = 4y^2
     
  8. Jan 24, 2010 #7

    tiny-tim

    User Avatar
    Science Advisor
    Homework Helper

    Hi Gringo123!

    [NOPARSE]Type "y2",[/NOPARSE] and it comes out y2 :smile:

    (or use the X2 tag just above the Reply box :wink:)
     
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook